Identification of reliable reference genes for quantitative real‐time PCR analysis of the Rhus chinensis Mill. leaf response to temperature changes. Issue 10 (15th September 2021) - Chen, Yanchao; Luo, Biao; Liu, Chuwei; Zhang, Zhengfeng; Zhou, Chi; Zhou, Ting; Peng, Guoping; Wang, Xujun; Li, Waichin; Wu, Chuan; Rao, Liqun; Wang, Qiming
Abstract : Rhus chinensis Mill. (RCM) is the host plant of Galla chinensis, which is valued in traditional medicine. Environmental temperature directly determines the probability of gallnut formation and RCM growth. At present, there is no experiment to systematically analyse the stability of internal reference gene (RG) expression in RCM. In this experiment, leaves that did not form gallnuts were used as the control group, while leaves that formed gallnuts were used as the experimental group. First, we conducted transcriptome experiments on RCM leaves to obtain 45 103 differential genes and functional enrichment annotations between the two groups. On this basis, this experiment established a transcriptional gene change model of leaves in the process of gallnut formation after being bitten by aphids, and RCM reference candidate genes were screened from RNA sequencing (RNA‐seq) data. This study is based on RCM transcriptome data and evaluates the stability of 11 potential reference genes under cold stress (4 °C) and heat stress (34 °C), using three statistical algorithms (geNorm, NormFinder, and BestKeeper). The results show that GAPDH1 + PP2A2/UBQ are stable reference genes under heat stress, while GAPDH1 + ACT are the most stable under cold stress. This study is the first to screen candidate reference genes in RCM and could help guide future molecular studies in this genus. Abstract : Appropriate and stable reference genes are important for normalization of gene expression. This study is based on Rhus chinensis Mill. transcriptome data and evaluates the stability of 11 potential reference genes under cold stress (4 °C) and heat stress (34 °C), using three statistical algorithms (geNorm, NormFinder, and BestKeeper). This study is the first to screen candidate reference genes in Rhus chinensis Mill. and could help guide future molecular studies in this genus.